Studi Perbandingan Metode SAW dan Metode AHP dalam Sistem Pendukung Keputusan Seleksi Kelayakan Calon Penerima Bantuan Progam Keluarga Harapan - Ningtyas, Yunida Ayu Kusuma; Diartono, Dwi Agus (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Program Keluarga Harapan (PKH) aims to provide regular financial support to Keluaga Miskin (KM). This research examines and compares two methods, Simple Additive Weighting (SAW) and Analytical Hierarchy Process (AHP), in a decision support system to assess the eligibility of PKH aid recipients. Sindurejo Village in Grobogan Regency, where PKH is implemented, faces challenges with manual assessments. The integration of both methods is expected to yield more objective, efficient, and accurate results in assessing PKH aid recipients. The research findings indicate that the choice between SAW and AHP methods depends on the specific needs and preferences of policymakers.